2007
DOI: 10.1101/gad.1561707
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analyses reveal properties of redundant and specific promoter occupancy within theETSgene family

Abstract: The conservation of in vitro DNA-binding properties within families of transcription factors presents a challenge for achieving in vivo specificity. To uncover the mechanisms regulating specificity within the ETS gene family, we have used chromatin immunoprecipitation coupled with genome-wide promoter microarrays to query the occupancy of three ETS proteins in a human T-cell line. Unexpectedly, redundant occupancy was frequently detected, while specific occupancy was less likely. Redundant binding correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
316
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(343 citation statements)
references
References 56 publications
25
316
0
2
Order By: Relevance
“…Our data revealed that ELF1, but not GABPα or FLI1 displayed strong enrichment in the MEIS1 promoter region both from EMSA and ChIP experiments in K562 cells. This was consistent with a recent genome wide ChIP study performed in a human T leukemia cell line, Jurkat, where ELF1 but not the other two ETS family members tested, GABPα and ETS1, was enriched at the MEIS1 promoter region (35). This strong association of ELF1 to the MEIS1 promoter region was also confirmed in human primary samples enriched with the hematopoietic stem/progenitor cells where MEIS1 was highly expressed.…”
Section: Discussionsupporting
confidence: 91%
“…Our data revealed that ELF1, but not GABPα or FLI1 displayed strong enrichment in the MEIS1 promoter region both from EMSA and ChIP experiments in K562 cells. This was consistent with a recent genome wide ChIP study performed in a human T leukemia cell line, Jurkat, where ELF1 but not the other two ETS family members tested, GABPα and ETS1, was enriched at the MEIS1 promoter region (35). This strong association of ELF1 to the MEIS1 promoter region was also confirmed in human primary samples enriched with the hematopoietic stem/progenitor cells where MEIS1 was highly expressed.…”
Section: Discussionsupporting
confidence: 91%
“…24 For example, whole genome studies with chromatin immunoprecipitation have allowed a better definition of consensus binding sites that have a much stronger predictive value. 25,26 Often these consensus sequences are much larger than the previously described or include influence from neighbouring nucleotides. Unfortunately, there are only a few of these studies and they do not include RUNX1.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The ChIP assay often yields low signals in comparison to negative controls, which can lead to inconclusive results; (2) it is difficult to determine the precise binding site for a factor because of the limited resolution of the assay; and (3) ChIP is not a functional assay and cannot by itself demonstrate the functional significance of a protein or modified histone found to be located at a genomic region of interest. This final limitation is especially problematic because many studies have now provided strong evidence that proteins associate with genomic sites at which they have no obvious function (Walter et al 1994;Li and Johnston 2001;Martone et al 2003;Phuc Le et al 2005;Beima et al 2006;Hollenhorst et al 2007;Dong et al 2008;Li et al 2008). It has been difficult to design experiments to rigorously test the possibility that specific histone modifications, as opposed to transcription factor-DNA interactions, are not functionally important at specific genomic locations at which they are found.…”
Section: Limitations Of the Chip Methodsmentioning
confidence: 99%